2021
DOI: 10.15244/pjoes/131203
|View full text |Cite
|
Sign up to set email alerts
|

Slope Stability Analysis to Develop Correlations between Different Soil Parameters and Factor of Safety Using Regression Analysis

Abstract: This paper generally deals with the slope stability analysis of soil and an easy way to stabilize the slope to achieve high shear strength. Correlations between Factor of Safety (FS) and soil parameters i.e. cohesion, friction and unit weight are developed in this paper. Correlations among factor of safeties in natural, stepped and nailed form are also developed using linear regression analysis. Soil is not a homogeneous material and its properties are changing in different conditions and in different places. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…With advances in computational technology and the development of geomechanical calculations, numerical modeling methods have made it possible to understand complex geotechnical problems (Hussain et al, 2018;Schweiger et al, 2019;Khan and Wang, 2021). Numerical calculations can mathematically solve a pattern of relationships between variables or parameters described in the form of functions.…”
Section: Creating the Modelsmentioning
confidence: 99%
“…With advances in computational technology and the development of geomechanical calculations, numerical modeling methods have made it possible to understand complex geotechnical problems (Hussain et al, 2018;Schweiger et al, 2019;Khan and Wang, 2021). Numerical calculations can mathematically solve a pattern of relationships between variables or parameters described in the form of functions.…”
Section: Creating the Modelsmentioning
confidence: 99%
“…Hence there is a need of analyzing slope stability under seismic loading.Marrapu and Jakka [1] created two distinct multiple regression models, verified their precision in the estimation using actual field data, and were satisfied with the findings. Wang and Khan [2] found correlations between various soil and slope parameters using the SLIDE software to forecast slope stability assessment. Zhou et al [3] investigate slope prediction using logistic regression and conclude that it is the best predictive approach for slope stability prediction.Huang and Peng [4] conducted a seismic slope stability analysis for saturated and unsaturated soil and found that dynamic pore water pressure influence is significant towards stability.…”
Section: Introductionmentioning
confidence: 99%